2013
DOI: 10.4209/aaqr.2012.12.0371
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Performance of the microAeth® AE51 and the Effects of Aerosol Loading on Its Measurement Results at a Traffic Site

Abstract: The new portable microAeth ® AE51 (AE51) is very useful for assessing occupational and environmental exposure to black carbon (BC) aerosols in epidemiological research. However, information about the performance of AE51 is limited. This study compares AE51 with the widely used, rack-mounted Aethalometer ® AE31 (AE31) by evaluating the real-time performance of these two instruments, as carried out at a traffic site. Additionally, an optimized noise-reduction averaging (ONA) algorithm is adopted to eliminate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 47 publications
2
49
2
Order By: Relevance
“…The DustTrak TM was fitted into a modified version of the aerosol sampling box described in [45], with an isokinetic flow splitter (TSI 3708) directing the airflow to different measurement pathways and Casella Apex Pro pumps providing the makeup flow to ensure correct size separation in the PM 2.5 inlet (BGI miniPM ® inlet 5011, 5 L·min −1 ). Smoke black carbon (BC) content was assessed using a microAeth AE51 [46].…”
Section: Smoke Measurements At Fixed Locationsmentioning
confidence: 99%
“…The DustTrak TM was fitted into a modified version of the aerosol sampling box described in [45], with an isokinetic flow splitter (TSI 3708) directing the airflow to different measurement pathways and Casella Apex Pro pumps providing the makeup flow to ensure correct size separation in the PM 2.5 inlet (BGI miniPM ® inlet 5011, 5 L·min −1 ). Smoke black carbon (BC) content was assessed using a microAeth AE51 [46].…”
Section: Smoke Measurements At Fixed Locationsmentioning
confidence: 99%
“…The accumulation of particles on the filter over time increases the absorbance, which is calculated relative to a reference cell. The attenuation IR is then transferred to mass concentration of black carbon (described in detail by Cheng and Lin (2013)). …”
Section: Measurements and Instrumentationmentioning
confidence: 99%
“…Moreover, Moteki et al (2014) showed that the abundance of coated BC particles among total BCcontaining particles can vary considerably with time. In addition, the abundance of coated BC parti cles varies with emission sources (China et al, 2014;China et al, 2013). Therefore, it is conceivable that the strength of the correlation declines if the abundance of coated BC particles increases in the afternoon.…”
Section: Comparison Between Surface Area Andmentioning
confidence: 99%
“…In general, some of the BC particles in the ambient air are considered to be coated with organic carbon (OC: China et al, 2014;China et al, 2013). If these particles are heavily coated with OC, their specific surface area is likely to decrease significantly.…”
Section: Comparison Between Surface Area Andmentioning
confidence: 99%
See 1 more Smart Citation